Development Of A Digital Physics Textbook Based On Multirepresentation To Help Students Apply The Concepts Of Sound And Light Waves : Pengembangan Buku Teks Fisika Digital Berbasis Multirepresentasi Untuk Membantu Siswa Menerapkan Konsep Gelombang Bunyi Dan Cahaya - U’ud Efendi (LPPM Institut Studi Islam Sunan Doe, 2023)
The aim of this study is to develop a digital physics textbook based on multirepresentation to assist grade 11 students in applying the concepts of sound and light waves in high school/islamic senior high school (SMA/MA) and to determine the feasibility and response of the students to the developed textbook. The research method used in this study is Research and Development and refers to the Borg and Gall development model. The digital textbook was validated by expert validators and two high school physics teachers. The digital textbook was tested on a limited basis with 26 students. The validation results of the digital textbook by expert validators and two high school physics teachers obtained an overall average score of 3.72 out of a scale of 4.00, which means that the digital textbook meets the valid criteria. The limited test results on 26 students showed that the percentage of the digital book trial results reached 92.66%, which means that the digital textbook met the practical criteria. These results indicate that the developed digital textbook is feasible for wider trials as it meets both valid and practical criteria.